TANGGUNGJAWAB MUTLAK TERHADAP KORPORASI DALAM PERTAMBANGAN TIMAH SEBAGAI KEGIATAN USAHA BERDASARKAN HUKUM LINGKUNGAN - Cendranita, Ivannia; Firmansyah, Hery (Universitas Muhammadiyah Ponorogo, 2024)
Tin mining is found in many major tin-producing areas such as Bangka and Belitung Islands, where this natural resource is one of the mainstays of local economic growth. The application of absolute liability also requires strong regulatory support, especially regarding the mechanism of proof and the determination of sanctions. In the Indonesian justice system, the process of proof is often an obstacle because there is no simple and efficient mechanism in environmental cases. This study uses a normative legal method with a legal analysis approach. This study focuses on the legislative aspect, considering the conceptual dimension and applicable regulations. The results of the study show that one of the steps taken is the Regional Regulation concerning the Coastal Area and Small Island Zoning Plan (RZWP3K), which applies a three-stage approach to supervising the use of marine resources in coastal areas and small islands, namely socialization, implementation, and supervision. In addition, the government is also taking steps to regulate the mining industry and ensure compliance with the law by involving various government agencies such as the Marine and Fisheries Service. By enforcing these regulations, the main objective is to maintain environmental sustainability, protect marine ecosystems, and minimize negative impacts on communities and natural resources.